Mobile communications: On standards, classifications and generations - Reza Tadayoni; Anders Henten; Jannick Sørensen (International Telecommunications Society (ITS), 2017)
The research question addressed in this paper is concerned with the manners in which the general technological progress in mobile communications is presented and the reasons for the differences in these manners of presentation. The relevance of this research question is that the different presentation modes create a degree of confusion in communications and discussions on mobile technologies. At the same time, it should be recognized that different manners of categorizing technologies illustrate the fact that categorizations are based on different purposes of the classification exercises. In common parlance, progress in mobile technologies is mostly referred to as generations. In the International Telecommunication Union (ITU), the classification terminology is that of International Mobile Telecommunication (IMT) standards. In the specialized standards body with a central position in the standardization of core mobile technologies, namely 3GPP (3rd Generation Partnership Project), the terminology of `releases' is used. In order to address the research question, the paper uses an analytical framework based on the differences and relationships between the concepts of standards, classifications and generations, and it examines the role of organizations involved in the development and marketing of new mobile technologies.
Keywords: 330